(untitled) - Daniela Bartoníčková; Dominika Kohanová; Katarína Žiaková (University of Ostrava, 2023)
Aim: To identify instruments measuring patient safety culture from the perspective of nursing students and to assess the content and reported psychometric properties of these instruments. Design: A narrative literature review. Methods: The search was carried out (according to institutional availability) in three scientific databases: ProQuest, PubMed, and Scopus. The search produced a total of 645 studies published up to May 2021. For data analysis, a summative content method was used. Results: We identified 12 instruments for measuring patient safety culture from the perspective of nursing students. Four instruments were designed to assess the perception of patient safety culture in the workplace, and eight instruments were designed for assessing nursing students' competencies in patient safety culture. Conclusion: The instruments share a core set of domains. However, details on conceptualisation, and methodological rigor differed substantially. Moreover, data on psychometric properties have not been published for most instruments. The absence of well-established instruments calls for further research.